Analisis Masalah Pengembangan Kue Cepak Kapung sebagai Daya Tarik Wisata Kuliner di Desa Terusan Kecamatan Maro Sebo Ilir - Laila Laila; Muhammad Refki Novesar (Journal of Tourism Sciences, Technology and Industry, 2026)
Cepak Kapung cake is one of the traditional specialties of Terusan Village, Maro Sebo Ilir Subdistrict, Batanghari Regency. This study aims to analyze the obstacles encountered and their impacts on the development of Cepak Kapung cake as a culinary tourism attraction. The study employed a qualitative approach using a purposive sampling technique involving eight informants. Data were collected through observation, semi-structured interviews, and document analysis. The findings revealed four main obstacles: the limited shelf life of the product (approximately 24 hours), the lack of generational succession among cake makers, inadequate infrastructure and limited integration with other tourist destinations, as well as weak digital marketing and promotional strategies. These obstacles are interconnected and affect production sustainability, destination competitiveness, the preservation of local cultural identity and heritage, and community economic development. The study recommends the adoption of food technology innovations, skills training programs for younger generations, the development of integrated infrastructure, and the strengthening of digital marketing capabilities through collaboration among local governments, tourism agencies, universities, and local communities. These efforts are expected to support the development of Cepak Kapung cake as a leading culinary tourism attraction.